Feminism and Islamic Tradition - Winifred Woodhull (Studies in 20th & 21st Century Literature, 1993)
"Feminism and Islamic Tradition" explores the territory mapped by Fatima Mernissi in Sultanes oublées (1990) and Le Harem politique: Le Prophète et les femmes (1987) in relation to that charted by Assia Djebar in her latest novel Loin de Médine (1991). The aim is to see why Maghrebian feminists as different as Mernissi and Djebar—a liberal democratic sociologist and a postmodern writer—have begun to move into Arab-Islamic cultural-political spaces which, until recently, have been occupied mainly by various Islamic fundamentalist factions and other right-wing groups such as conservative nationalists in the Maghreb. The essay delineates the change between these writers' recent work and their earlier writing. It then considers their revaluations of Islamic tradition in light of the work of feminists and other progressives in Muslim countries who are resisting the growing power of Islamic fundamentalisms in various geopolitical contexts while at the same time contesting western orientalist views of Islam and Muslim culture.
Keywords: Fatima Mernissi; Sultanes oublées; Le Harem politique: Le Prophète et les femmes; Assia Djebar; Loin de Médine; feminists; feminism; liberal; conservative; feminist literature; women; conservative nationalist; Maghreb; Islamic tradition; Muslim progressives; Islamic fundamentalism; Islamic culture; Muslim culture